Rancangan Penggunaan Drone Untuk Mengantarkan Paket - Sofyan Mufti Prasetiyo; Rachmadi Setiawan; Gilang Putra Ramadhan; Rian Pradifta Setiawan (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The shipping system is currently less efficient in shipping speed and not environmentally friendly, so it takes a long time to receive packages and increase air pollution. In this study create a new transportation that can accelerate the delivery of goods and environmentally friendly namely that is delivery drones. The advantages of using a drone are fuel-friendly, time efficiency. In this study fuzzy methods and mapping in the control system of the drone are used. In this study produce drones that can deliver goods automatically following a predetermined path.